(untitled) (Journal of Ideas in Health, 2021)
Background: Mucopolysaccharidoses (MPSs) are a group of lysosomal storage diseases, resulted from glycosaminoglycans’ breakdown failure (GAGs). The study aims to determine the presence of thrombocytopenia, its prevalence, clinical implication, and correlation with the types of MPSs and with the types of glycosaminoglycans storage. Methods: A retrospective cross-sectional study of complete blood count data was conducted among 108 children with a confirmed diagnosis of MPS in the National Medical Research Center for Children’s Health, Moscow, Russian Federation. STATISTICA 10 (Stat Soft, Inc. 1984-2011) was used for statistical analysis. A p-value of ≤0.05 was considered significant. Results: The median age of children was 65 [IQR: 41; 102] months, range: 3 – 102 months. The male to female ratio was 3:1. The prevalence of fluctuating or persistent thrombocytopenia in all children with MPS was 19.0%. Thrombocytopenia occurred in patients with MPS I (14.0%), II (19.0%), and III (31.0%). Neither of the patients with MPS IV nor VI demonstrated low platelet count. There was a non-significant predominance (P=0.068) of thrombocytopenia frequency in patients with heparan sulfate storage (22.0%) compared with patients without heparan sulfate burden (0%). Conclusion: Routine checkups of patients with MPSs must include complete blood count with platelet measurement. Cases of thrombocytopenia that requiring treatment, immunomodulatory/ immunosuppressive therapy should be considered. Further research is needed to look for the laboratory confirmation of autoimmune variants of HIT in patients with MPS I, II, III.